A New Approach to the Uniqueness of Equilibrium - Grandmont, J. M.; Kirman, A. P.; Neuefeind, W. (Review of Economic Studies, 1974)
J. M. Grandmont, A. P. Kirman, W. Neuefeind; A New Approach to the Uniqueness of Equilibrium12, The Review of Economic Studies, Volume 41, Issue 2, 1 April 1974